Archived U-Pb (zircon) dates from southern New Brunswick - McLeod, Malcolm; Johnson, Susan; Krogh, Tom (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT U-Pb (zircon) ages for eight samples from southern New Brunswick were determined during the early 1990's as part of a regional mapping and correlation program. Although most of the dates have been subsequently quoted in the literature through personal communications, and some preliminary isochron diagrams have been incorporated in papers, the results have not been published in their entirety. The units sampled and best estimates for their ages are the Lobster Brook Formation (554 ± 6 Ma), Leavitts Head Formation (554 ± 3 Ma), Ragged Falls Suite (553 ± 2 Ma), Mosquito Lake Road Formation (514 ± 2 Ma, maximum age), Bayswater Formation (436 ± 3 Ma), Centreton Granite (437 ± 3 Ma), felsic dyke of North Head, Grand Manan Island (396+3/-2 Ma), and Lake George Cupola, Lake George Mine (414 ± 2 Ma).